Rekontekstualisasi Tafsir Pembebasan Perspektif Farid Esack dalam Menghadapi Ancaman VUCA di Abad ke-21 - Ambo' Dalle, Abd. Rahman; Nasrulloh Nasrulloh (Holistik Analisis Nexus, 2024)
This study explores the recontextualization of Farid Esack's liberation theology in addressing the challenges of VUCA (Volatility, Uncertainty, Complexity, Ambiguity) in the 21st century. Esack, a progressive Muslim theologian, focuses on social justice, pluralism, and advocacy for the oppressed as a response to global uncertainties arising from economic instability, political conflict, and environmental crises. The research employs critical discourse analysis to examine how Esack's interpretation can provide a critical framework for Muslims to respond to the changing times full of uncertainty. The findings reveal that Esack's liberation theology offers an inclusive foundation for building global solidarity across religions and nations, emphasizing principles of social justice and equality. Esack's approach also promotes flexibility in religious interpretation, which is crucial in facing moral ambiguities and socio-political complexities in the modern era. This study aims to contribute to the development of a more contextual and responsive Islamic interpretation that addresses global challenges.